2022
DOI: 10.1038/s42003-022-04002-7
|View full text |Cite
|
Sign up to set email alerts
|

Human thymoma-associated mutation of the GTF2I transcription factor impairs thymic epithelial progenitor differentiation in mice

Abstract: Few human tumours present with a recurrent pathognomonic mutation in a transcription factor. Thymomas are an exception, with the majority of some subtypes exhibiting a distinct somatically acquired missense mutation in the general transcription factor GTF2I. Co-dominant expression of wild-type and mutated forms of Gtf2i in the mouse thymic epithelium is associated with aberrant thymic architecture and reduced thymopoietic activity. Phenotypic and molecular characterization of the mutant epithelium indicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Most THs contain subtype-specific mixtures of functional, albeit defective, cells with cortical and medullary differentiation, suggesting their origin from bipotent thymic progenitors [ 7 ]. The absence of the medullary autoimmune regulator gene (AIRE) in 95% of THs and recent studies in mice with mutations in GTF2I have provided experimental support for this hypothesis [ 8 , 9 ]. Therefore, it is to be expected that many of the programs and factors that govern the development and maintenance of the normal thymus are also important in the pathogenesis of THs.…”
Section: Disturbed Thymic Developmental Programs In Thymomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Most THs contain subtype-specific mixtures of functional, albeit defective, cells with cortical and medullary differentiation, suggesting their origin from bipotent thymic progenitors [ 7 ]. The absence of the medullary autoimmune regulator gene (AIRE) in 95% of THs and recent studies in mice with mutations in GTF2I have provided experimental support for this hypothesis [ 8 , 9 ]. Therefore, it is to be expected that many of the programs and factors that govern the development and maintenance of the normal thymus are also important in the pathogenesis of THs.…”
Section: Disturbed Thymic Developmental Programs In Thymomasmentioning
confidence: 99%
“…However, a recent study using microdissected tissues reported high mutation rates of 42% also in type B thymomas [ 30 ]. In endogenous mouse models with the specific expression of mutated GTF2I in FOXN1+ thymic epithelial cells, the mutation causes an incomplete block of TEC differentiation with the accumulation of immature TECs and reduced thymopoietic activity [ 8 ] and leads to the formation of thymomas resembling WHO type B1 and B2 THs in aged animals [ 31 ]. The mutation consistently confers increased resistance to apoptosis, tolerance to DNA damage, and alterations in cell cycle regulation with enrichment of the MYC, E2F, and G2M checkpoint target genes [ 8 , 31 , 32 ].…”
Section: Disturbed Thymic Developmental Programs In Thymomasmentioning
confidence: 99%
“…59,119 Two recent studies successfully demonstrated the functional significance of the Gtf2i mutation in TECs in vivo by establishing transgenic mice harboring the TECspecific Gtf2i mutation corresponding to human GTF2I L424H. 120,121 Specifically, these mice developed a disorganized thymus where the border between the cortex and the medulla became obscured, and progenitors between cTECs and mTECs expanded, which could form tumors. 120 These innovative studies strongly argue that the most frequent mutation in TETs not only confers proliferative activities but induces differentiation abnormalities in TECs.…”
Section: Genetic Signatures Of Tets Gtf2i Mutations In Thymomas and T...mentioning
confidence: 99%
“…55,59 Thus, it is perhaps a good time to try to incorporate such lineage-related phenotypes in the definition of TET subtypes. In particular, considering the prevalence and impact on cellular biology 55,120,121 and the fact that combined histological-molecular classification has gained popularity, the presence/absence of GTF2I mutations might be added to the nomenclatures of some TET subtypes, as with IDH mutations in glial tumors. 130 To this end, GTF2I mutation must be routinely examined in daily practice, for example, by a mutation-specific antibody or by enrolling this gene in a genetic panel of, for example, lung cancers.…”
Section: Future Perspective For Classification Of Tetsmentioning
confidence: 99%
See 1 more Smart Citation